2002
DOI: 10.1063/1.1510444
|View full text |Cite
|
Sign up to set email alerts
|

Imaging O(3P)+alkane reactions in crossed molecular beams: Vertical versus adiabatic H abstraction dynamics

Abstract: Articles you may be interested inExploring the dynamics of reaction N + SiH 4 with crossed molecular-beam experiments and quantum-chemical calculations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
40
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…For the reaction of O( 3 P) + butane, Liu et al observed a similar trend and concluded that 4−5 kcal·mol −1 was not available for the product alkyl recoil. 63 Large polyatomic systems such as those studied here possess several repositories for the excess energies, in particular vibrations or rotations of the alkyl radical product. A simple hybrid Franck−Condon/impulsive model has been developed to account for the rotational excitation E rot of the alkyl radical product in the F + ethane reaction: 93…”
Section: Discussionmentioning
confidence: 99%
“…For the reaction of O( 3 P) + butane, Liu et al observed a similar trend and concluded that 4−5 kcal·mol −1 was not available for the product alkyl recoil. 63 Large polyatomic systems such as those studied here possess several repositories for the excess energies, in particular vibrations or rotations of the alkyl radical product. A simple hybrid Franck−Condon/impulsive model has been developed to account for the rotational excitation E rot of the alkyl radical product in the F + ethane reaction: 93…”
Section: Discussionmentioning
confidence: 99%
“…This work builds upon previous crossed-beamreactive-scattering studies of F + CH 4 /CD 4 by Liu, Harper, and others, [44][45][46] REMPI studies of Cl+ alkanes of Zare, OrrEwing, Kitsopolous, 38,39,47,48 as well as extensive studies of O͑ 3 P͒ + methane and nonmethane hydrocarbons by Suits, McKendrick, and others. 29,41,49,50 The work also builds on early FTIR studies of the F + C 2 H 6 system by Setser and co-workers, who report relative HF͑v =1,2,3͒ vibrational energy distributions, 51 although under incompletely "arrested" rotational relaxation conditions.…”
Section: Introductionmentioning
confidence: 96%
“…This has provided further incentive for atom + polyatom crossed beam studies with spectroscopic-based detection of products, as explored by Liu, Zare, Suits, Valentini, and others. [37][38][39][40][41] Counterbalancing these challenges, however, is the substantially richer world of reaction dynamics that opens up at the atom+ polyatom level. Consider, for example, a simple atom abstraction in a highly exothermic atom+ polyatom system.…”
Section: Introductionmentioning
confidence: 98%
“…The first method uses a calibration reaction for which the DCS is known from CMB experiments, 26,27 and the second is to use the outcomes of a comprehensive Monte-Carlo (MC) simulation of the experiments that is similar in spirit to the approach used by Suits and coworkers for a related experimental design. 80 In both cases an angular correction function is generated, and the two are similar in form and magnitude. The details of the first method have been described elsewhere, 32 but, in brief, an experimental angular correction function was obtained by comparison of dual molecular beam images for reaction (4) with CMB and VMI results reported by Huang et al 27 at a similar collision energy.…”
Section: Dual Beam Imagingmentioning
confidence: 99%